In-situ transformed nano-underlayer current collector and preparation method thereof
Patent Information
- Application Number
- CN202611508609.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-28
- Publication Date
- 2026-10-30
AI Technical Summary
由于铝箔表面的自然氧化层组成和厚度不均,钠通常优先在局部缺陷处成核,容易造成沉积不均、局部失去接触以及循环过程中界面阻抗持续增大
(1)本申请提供了一种原位转化型纳米底层集流体的制备方法,区别于现有技术裸铝箔及外加颗粒型底层工艺,本申请采用膦酸型表面反应前驱体与氟化氢铵先后完成有限活化和膦酸配位成层,使纳米底层通过 Al-O-P、Al-F 或 Al-O-F 结合结构与铝箔表层连续连接,降低循环过程中的脱层和局部失去接触风险,其作用机理如下:
Smart Images

Figure CN123017989A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of negative electrode current collector preparation technology for negative electrode-free sodium metal batteries, specifically to an in-situ conversion type nano-bottom current collector and its preparation method. Background Technology
[0002] In a non-negative electrode sodium metal battery, no sodium metal negative electrode is provided during assembly. During the first charge, sodium ions released from the positive electrode are reduced and deposited on the surface of the negative electrode current collector. Due to the uneven composition and thickness of the natural oxide layer on the aluminum foil surface, sodium usually preferentially nucleates at local defects, which can easily lead to uneven deposition, local loss of contact, and a continuous increase in interfacial impedance during cycling.
[0003] Known technologies mainly employ solutions such as adding external coatings or surface chemical treatments to improve the performance of current collectors, aluminum-based materials, or aluminum-plastic films to address the aforementioned problems.
[0004] CN117810456A discloses a method for preparing a multilayer composite current collector. This method first passivates an aluminum or copper layer, then bonds a metal layer to a polymer film using an acid-modified polyolefin layer. The resulting passivation layer improves the acid resistance of the metal layer and the bonding stability between the metal layer and the polymer film. The final product of this method is a seven-layer composite structure centered on the polymer film. Its technical objective is to reduce interlayer delamination under the influence of the electrolyte. This technical solution adds a polymer film, rather than using the treated aluminum surface as the sodium deposition interface for a negative electrode-less sodium metal battery.
[0005] CN120149422A discloses a current collector for a negative electrode-free sodium-ion battery, which involves sequentially coating a conductive layer and a carboxylic acid metal salt layer onto the surface of an aluminum or copper foil. The conductive layer has a thickness of 1-3 μm, and the carboxylic acid metal salt layer has a thickness of 1-5 μm. During the initial sodium plating process, the carboxylic acid ligands are converted to form a carboxylic acid-sodium interface layer. However, the functional layer in this scheme is formed by coating and drying a slurry made from carbon black, carboxylic acid metal salt, and binder layer by layer, which is an external material layer. It does not require the aluminum foil surface to participate in the layering reaction, nor does it use the treated aluminum surface as the sodium deposition interface for the negative electrode-free sodium metal battery.
[0006] CN120809831A discloses a method for preparing aluminum-based current collectors for lithium batteries. This method involves polishing, alkaline washing, acid washing, and activation of aluminum foil, followed by coating with a zinc-aluminum alloy slurry, hot-dip galvanizing, and electrophoretic deposition. The innovation of this technical solution lies in the subsequent formation of the alloy slurry, the 5-10 μm hot-dip galvanized layer, and the electrophoretic coating; the surface of the aluminum foil treated is not the ultimately exposed sodium deposition interface. Summary of the Invention
[0007] The first aspect of this application is to provide an in-situ conversion type nano-substrate current collector.
[0008] The technical solution adopted in this application is as follows: An in-situ conversion type nano-substrate current collector includes an aluminum foil substrate and a nano-substrate disposed on the surface of the aluminum foil substrate, wherein the nano-substrate is formed by in-situ conversion from the surface of the aluminum foil substrate.
[0009] The in-situ conversion refers to treating the surface of the aluminum foil substrate with a conversion solution, wherein the conversion solution includes at least a phosphonic acid-type surface reaction precursor and ammonium hydrogen fluoride (NH4HF2).
[0010] The nano-substrate includes an anchoring inner layer and a regulating outer layer. The anchoring inner layer is located on the side close to the aluminum foil substrate, and the regulating outer layer is located on the outside of the anchoring inner layer, i.e., on the side facing the electrolyte.
[0011] The anchoring inner layer contains one or more of Al-OP, Al-F and Al-OF bonding structures and is continuously connected to the surface layer of the aluminum foil substrate.
[0012] The outer layer of regulation is mainly composed of an aluminum phosphonate network, and retains P-OH, P=O, or boron- or nitrogen-containing polar sites.
[0013] A second aspect of this application aims to provide a method for preparing an in-situ conversion type nano-substrate current collector, comprising the following steps: (1) Provide aluminum foil with a thickness of 8-20μm, first degrease it, and then clean it with deionized water; (2) Prepare a conversion solution, wherein the conversion solution contains at least a phosphonic acid-type surface reaction precursor and ammonium hydrogen fluoride (NH4HF2), and adjust the pH of the conversion solution to 2.5-4.5; (3) Contact at least one side of the aluminum foil with the conversion solution at 20-60℃ for 10-180s; then rinse with deionized water, pre-dry at 60-100℃ for 0.5-5min, and then heat-treat at 100-160℃ for 1-10min. (4) Cool and roll up to obtain an in-situ conversion type nano bottom current collector.
[0014] Further settings are as follows: In step (1): The aluminum foil is degreased using ethanol or a weakly alkaline aqueous solution.
[0015] In step (2): The conversion solution uses deionized water as a solvent, and based on the total mass of the conversion solution, the mass content of the phosphonic acid-type surface reaction precursor is 0.2%-2.0%; the mass content of ammonium bifluoride (NH4HF2) is 0.01%-0.15%.
[0016] The phosphonic acid-type surface reaction precursor is selected from any one or a combination of 1-hydroxyethylidene-1,1-diphosphonic acid (HEDP), aminotrimethylenephosphonic acid, phytic acid, and vinylphosphonic acid; based on the total mass of the conversion solution, the mass content of the phosphonic acid-type surface reaction precursor is preferably 0.4%-1.5%.
[0017] Based on the total mass of the conversion liquid, the mass fraction of ammonium bifluoride (NH4HF2) is preferably 0.02%-0.08%.
[0018] Ammonia or dilute phosphoric acid is used as a pH adjuster to adjust the pH of the conversion solution to 2.5-4.5, preferably 3.0-3.8.
[0019] Furthermore, the conversion solution also contains boric acid or borates, with a mass fraction of 0.02%-0.3% based on the total mass of the conversion solution. The purpose of adding boric acid or borates is to adjust the boron-containing polar sites on the outer layer.
[0020] In step (3): The aluminum foil is brought into contact with the conversion solution by means of immersion, micro-gravure coating or roller coating, slot coating or roller coating. It is preferred to use micro-gravure roller coating to bring one side of the aluminum foil into contact with the conversion solution at 30°C for 30 seconds.
[0021] The pre-drying process is carried out at a temperature of 80°C for 2 minutes.
[0022] The heat treatment was performed at a temperature of 130°C for 3 minutes.
[0023] The third objective of this application is to provide an in-situ conversion type nano-bottom current collector for use in a negative electrode-free sodium metal battery.
[0024] Compared with the prior art, this application has the following beneficial effects: (1) This application provides a method for preparing an in-situ conversion type nano-bottom current collector, which differs from the existing bare aluminum foil and external particulate bottom layer process. This application uses a phosphonic acid type surface reaction precursor and ammonium bifluoride to complete limited activation and phosphonic acid coordination layering in sequence, so that the nano-bottom layer is continuously connected to the aluminum foil surface through Al-OP, Al-F or Al-OF bonding structure, reducing the risk of delamination and local loss of contact during the cycling process. Its mechanism of action is as follows: After degreasing and cleaning, aluminum foil retains a hydroxylated natural oxide layer on its surface. NH4HF2 provides small amounts of HF and F in water. -The process preferentially dissolves and removes loose, unevenly composed alumina, generating substances containing Al-F and Al-OF bonds and exposing new Al-OH sites on the surface. This activation process is limited by NH4HF2 concentration, contact time, and temperature, and only acts on a limited depth region on the outermost side of the aluminum foil. The phosphonic acid groups of the phosphonic acid-type surface reaction precursor (such as HEDP) then undergo ligand exchange and dehydration condensation with the surface Al-OH, forming Al-OP bonds; simultaneously, a small amount of Al dissolved during the activation process... 3+ It coordinates with phosphonate ions to form a continuous aluminosilicate network, ultimately forming an outer layer containing Al-OP, P-OH, and P=O bonds during drying. The above reaction can be represented by the following simplified formula: ; In the formula: R represents an organic group in the HEDP molecule that connects two phosphonic acid groups.
[0025] Part F - Al-F or Al-OF structures are formed with surface aluminum or oxygen-containing aluminum species, mainly distributed on the side closer to the aluminum foil; the HEDP-derived Al-OP, P-OH, and P=O structures are mainly distributed on the side closer to the electrolyte; after cleaning to remove unreacted free precursors, the residual Al-OH and P-OH are further dehydrated and condensed by heat treatment at 100-160℃ to obtain a nano-bottom layer with gradually changing composition from the inside to the outside.
[0026] The nano-substrate of this application includes an anchoring inner layer and a regulating outer layer. The anchoring inner layer is formed by the surface layer of the aluminum foil substrate participating in the reaction. The bonding between the interfaces mainly relies on Al-OP, Al-F or Al-OF bonding and continuous compositional transition, rather than simply relying on the binder. This can reduce the risk of the substrate peeling or local loss of contact during sodium deposition / peeling and temperature changes.
[0027] (2) The preparation method of the in-situ conversion type nano bottom current collector of this application adopts a water-based low-concentration conversion solution and a heat treatment process below 160°C, which can be seamlessly connected with the continuous coating, rinsing, drying and winding process of aluminum foil.
[0028] (3) The in-situ conversion nano-bottom current collector prepared in this application has been experimentally verified to effectively reduce the sodium deposition nucleation overpotential and improve the first-cycle coulombic efficiency, 25℃ cycling stability and 45℃ cycling stability when applied to NFPP-based polyanionic cathode and 1.0 mol / L NaPF6 / G2 electrolyte system.
[0029] The present application will be further described below with reference to the accompanying drawings and specific embodiments. Attached Figure Description
[0030] Figure 1 This is a schematic diagram of the structure of the in-situ conversion nano-substrate current collector of this application; Figure 1 In the diagram: the dashed line represents the original aluminum foil surface before in-situ conversion, t1 represents the surface conversion depth of the aluminum foil substrate, and t2 represents the total thickness of the nano-layer formed after in-situ conversion.
[0031] Figure 2 This is a schematic diagram of the in-situ conversion nano-substrate current collector preparation method of this application.
[0032] Figure 3 The high-resolution XPS spectrum of P 2p of the sample prepared in Example 1 without G2 immersion is shown. In the figure: the black line represents the unetched area on the surface, and the red line represents Ar. + The inner layer position after 30 seconds of etching.
[0033] Figure 4 The image shows the F 1s high-resolution XPS spectrum of the sample prepared in Example 1 without G2 immersion; in the figure: the black line represents the unetched area on the surface, and the red line represents Ar. + The inner layer position after 30 seconds of etching.
[0034] Figure 5 The high-resolution XPS spectrum of P 2p of the sample prepared in Example 1 after immersion in G2 for 72 hours, rinsing with fresh G2, and vacuum drying; in the figure: the black line represents the unetched area on the surface, and the red line represents Ar. + The inner layer position after 30 seconds of etching.
[0035] Figure 6 The F 1s high-resolution XPS spectrum of the sample prepared in Example 1 after immersion in G2 for 72 hours, rinsing with fresh G2, and vacuum drying; in the figure: the black line represents the unetched area on the surface, and the red line represents Ar. + The inner layer position after 30 seconds of etching.
[0036] Figure 7 The image shows a TOF-SIMS 3D signal image of the sample prepared in Example 1, with the collection mode being cation mode and the collected ion being AlPO2. + The signal strength is shown in the diagram on the right. The black area represents the area with no signal on the aluminum foil substrate.
[0037] Figure 8 The image shows a TOF-SIMS 3D signal image of the sample prepared in Example 1, with the collection mode being anion mode and the collected ion being F. - The signal strength is shown in the diagram on the right. The black area represents the area with no signal on the aluminum foil substrate.
[0038] Figure 9 This is a comparison chart of the 25°C cycling performance of the current collectors prepared in Example 1 and Comparative Example 1 of this application. Detailed Implementation
[0039] The present application will be further described below with reference to the accompanying drawings and embodiments. Unless otherwise specified, the raw materials, equipment and testing methods used in the embodiments are all conventional raw materials, equipment and methods in the art.
[0040] First, combined Figure 1 This application describes the basic structure of an in-situ conversion type nano-substrate current collector, which includes an aluminum foil substrate 1 and a nano-substrate disposed on the surface of the aluminum foil substrate 1, wherein the nano-substrate is formed by in-situ conversion from the surface of the aluminum foil substrate 1.
[0041] The in-situ conversion involves treating the surface of the aluminum foil substrate 1 with a conversion solution, which includes a phosphonic acid-type surface reaction precursor and NH4HF2.
[0042] The nano-bottom layer includes an anchoring inner layer 2 and a regulating outer layer 3. The anchoring inner layer 2 is located on the side close to the aluminum foil substrate 1, and the regulating outer layer 3 is located on the outside of the anchoring inner layer 2, i.e., on the side facing the electrolyte.
[0043] Anchoring inner layer 2: During the limited activation process on the aluminum foil surface, some F - The phosphonic acid precursor forms Al-F or Al-OF structures with the surface aluminum or oxygen-containing aluminum species, exposing new Al-OH sites on the surface. The phosphonic acid groups of the phosphonic acid-type surface reaction precursor undergo ligand exchange, coordination, and dehydration condensation with the activated and exposed Al-OH sites to form an Al-OP structure. Since the above reaction begins from the aluminum foil surface, the anchored inner layer 2 continuously connects with the unconverted aluminum matrix at the conversion front and spans... Figure 1 The original aluminum foil surface is shown.
[0044] Regulation of outer layer 3: On the one hand, the phosphonic acid groups of the phosphonic acid-type surface reaction precursor undergo ligand exchange, coordination, and dehydration condensation with the activated and exposed Al-OH to form an Al-OP structure; simultaneously, the dissolved Al... 3+ Coordinated with phosphonate ions, an aluminosilicate network is formed adjacent to the anchoring inner layer 2. After rinsing to remove unreacted free precursors, pre-drying and heat treatment further dehydrate and condense the residual Al-OH and P-OH, forming a regulating outer layer 3 on the side of the anchoring inner layer 2 away from the aluminum foil. The regulating outer layer 3 is mainly composed of an aluminosilicate network and retains polar structures such as P-OH and P=O. Figure 1 The outer side of the aluminum foil surface faces the electrolyte.
[0045] The following combination Figure 2 The present application describes a method for preparing an in-situ conversion type nano-bottom current collector.
[0046] Example 1
[0047] A method for preparing an in-situ conversion type nano-substrate current collector includes the following steps: (1) Take a battery-grade aluminum foil with a thickness of 12μm, wipe it with ethanol to remove oil, and then rinse it with deionized water.
[0048] (2) Preparation of conversion solution: Based on the total mass of the conversion solution, the mass fraction of HEDP is 0.60%, the mass fraction of NH4HF2 is 0.03%, and the remainder is deionized water. Then, the pH is adjusted to 3.2 with ammonia.
[0049] (3) Keep the conversion solution at 30°C, use micro-concave roller coating to make one side of the aluminum foil contact the conversion solution for 30s, then rinse quickly with deionized water for 5s, pre-dry at 80°C for 2 min, and then heat treat at 130°C for 3 min.
[0050] (4) Cool and roll up to obtain an in-situ conversion type nano bottom current collector.
[0051] Product characterization: (1) XPS testing was performed using a monochromatic Al Kα light source: the surface test location was the unetched sample surface, and the inner test location was the sample surface with an Ar Kα light source. + The position after 30 seconds of etching; the equivalent removal depth corresponding to 30 seconds is 5±1 nm. High-resolution spectra of P 2p and F1s were acquired respectively, and the test results correspond to... Figures 3-6 .
[0052] like Figures 3-6 As shown: XPS depth analysis reveals that the in-situ conversion nano-current collector prepared in this application has a high P element content, and after 30 s etching (~5 nm), the relative F element content is also high. Figure 5 and Figure 6 As shown: After G2 immersion and vacuum drying removal, P and F elements can still be detected, and the F element content is high after 30s of etching, indicating that the layer is not a simple residue of unreacted precursor.
[0053] (2) Quantitative analysis of surface P and F atomic content using XPS: The sample was soaked in diethylene glycol dimethyl ether G2 for 72 hours, rinsed with fresh G2 and dried under vacuum conditions, and then the surface atomic content of P and F was determined under the same XPS conditions. The retention rate was calculated based on the ratio of atomic content after soaking to atomic content before soaking.
[0054] Testing revealed that the total atomic content of P and F in the outer layer of the sample prepared in Example 1 was controlled to be 6.8 at%, with P accounting for 4.6 at% and F for 2.2 at%. After the nano-bottom layer was immersed in diethylene glycol dimethyl ether G2 for 72 hours, rinsed with fresh G2, and vacuum dried, the surface atomic content retention rates of P and F were 80.4% and 77.3%, respectively, both not lower than 70% of the levels before immersion.
[0055] (3) TOF-SIMS (Time-of-Flight-Secondary Ion Mass Spectrometry) was used for testing. The surface test location was the unetched sample surface, and the innermost test location was the Ar-12 sample surface. + The location of the ion clusters after 30 seconds of etching was determined. Two locations were selected for testing in both cation and anion modes, and cation and anion signals were collected respectively. Since the etching of ion clusters cannot be equivalent to depth in terms of time, only AlPO2 before and after etching was observed. + and F - The concentration relationship, the test results correspond to Figures 7-8 .
[0056] Figures 7-8 The image shows a TOF-SIMS diagram of the prepared in-situ conversion nanolayer current collector: AlPO2 can be collected in cation mode. + The signal was observed to be enriched on the surface, and its intensity decreased with increasing etching depth; the anion mode could collect F. - Signals were observed, and the signal intensity increased rapidly with increasing etching depth, accumulating at the bottom. The absence of signal areas indicates that the etching has penetrated the entire in-situ conversion surface layer and reached the aluminum foil surface. Both cationic and anionic signals indicate that the in-situ conversion layer is divided into an anchoring inner layer (F...). - Enrichment) and regulation of the outer layer (AlPO2) + Enrichment).
[0057] The above tests demonstrate that the in-situ conversion-type nanolayer current collector of this application forms a nanolayer consisting of an anchoring inner layer and a regulating outer layer through in-situ conversion on the aluminum foil surface, rather than by sequentially adding two coating layers to the aluminum foil surface. The oxyphosphonic acid groups and fluorinated aluminum species in the regulating outer layer have strong polarity and can change the adsorption and initial nucleation distribution of solvated sodium ions on the aluminum foil surface.
[0058] Examples 2-8 To investigate the effects of different conversion solution preparation and processing techniques on the performance of in-situ conversion nano-substrate current collectors, experiments as shown in Examples 2-8 were conducted, and the experimental conditions are shown in Table 1.
[0059] Table 1. Preparation and processing techniques of conversion fluid in different embodiments .
[0060] Comparative Example 1 Battery-grade aluminum foil with a thickness of 12μm is used, and it is cleaned only with ethanol and deionized water without surface conversion treatment.
[0061] Comparative Example 2 Battery-grade aluminum foil with a thickness of 12 μm was used. After cleaning with ethanol and deionized water, an additional particulate layer composed of conductive carbon black and PVDF in a mass ratio of 80:20 was coated on the surface of the cleaned aluminum foil. The thickness after drying was 310 nm.
[0062] Comparative Example 3 The preparation method is the same as in Example 1, except that: a conversion solution with a mass fraction of 2.50% HEDP, 0.20% NH4HF2, and pH 2.5 is used, and the solution is contacted at 50°C for 300 s and then treated at 180°C for 10 min.
[0063] Comparative Example 4 The preparation method is the same as in Example 2, except that only HEDP solution of the same concentration is used in the conversion solution, but NH4HF2 is not added.
[0064] Comparative Example 5 The preparation method is the same as in Example 2, except that only 0.04% NH4HF2 aqueous solution is used in the conversion solution, but no phosphonic acid precursor is added.
[0065] Application Examples The current collectors prepared in the aforementioned examples and comparative examples were applied to sodium metal batteries without negative electrodes, and their electrochemical performance was tested.
[0066] A sodium metal battery without a negative electrode consists of a positive electrode, a negative electrode current collector, a separator, and an electrolyte.
[0067] Positive electrode: NFPP / C material, namely Na4Fe3(PO4)2P2O7 / C material, is used. NFPP / C, conductive carbon black and PVDF are mixed at a mass ratio of 94:3:3, and NMP is used as a solvent to make a slurry. Then, it is coated onto the positive electrode aluminum foil, vacuum dried at 120℃ for 12 h, and then rolled and cut into sheets to obtain the positive electrode sheet.
[0068] Separator: Polyolefin separator is used.
[0069] Electrolyte: 1.0 mol / L NaPF6 in diethylene glycol dimethyl ether solution (G2).
[0070] Negative electrode current collector: When using the current collector prepared in the aforementioned examples and comparative examples, no sodium metal or sodium storage active material is pre-placed on the negative electrode side during the assembly of a sodium metal battery without a negative electrode.
[0071] Battery assembly: The positive electrode, separator, and negative electrode current collector are stacked in sequence to obtain a bare cell; the bare cell is packaged in an aluminum-plastic film bag to obtain a dry cell; then the electrolyte is injected into the dry cell to complete the packaging; and then the cell undergoes liquid injection, formation, and shaping processes to obtain a sodium metal battery without a negative electrode.
[0072] Electrochemical performance testing: The battery underwent two formation cycles at 25℃ and 0.05 C. The coulombic efficiency of the first cycle was calculated as the ratio of the first-cycle discharge capacity to the first-cycle charge capacity. Cycling at 25℃ and 45℃ was performed at 1C within a voltage range of 1.5-3.5 V. Nucleation overpotential was measured using a half-cell with a sodium sheet as the counter electrode and the current collector as the working electrode. The difference between the maximum voltage value achievable at the instant current was applied and the voltage value after voltage stabilization was collected. The applied current density was 0.5 mA / cm², and the deposition capacity was 1.0 mAh / cm².
[0073] The formula for calculating capacity retention is as follows: Capacity retention rate = Discharge capacity of the corresponding cycle / Discharge capacity of the first cycle after activation × 100%.
[0074] The test results are shown in Table 2.
[0075] Table 2 .
[0076] As shown in Table 2: (1) The in-situ conversion nano-bottom current collectors prepared in Examples 1-8 of this application have significantly better electrochemical performance than the current collectors of Comparative Examples 1-5.
[0077] Comparative Example 1 lacks an in-situ transformation layer and exhibits the highest nucleation overpotential. Figure 9 The capacity retention curves of Example 1 and Comparative Example 1 under charge-discharge cycles at 25°C show that the cycle stability of Example 1 is much better than that of Comparative Example 1.
[0078] Although Comparative Example 2 contains an external conductive particle layer, it lacks the surface conversion depth of aluminum foil, resulting in limited long-term cycling improvement.
[0079] Comparative Example 3 has a layer thickness and conversion depth that both exceed the preferred range. Although the content of heterogeneous elements on the surface is high, the nucleation overpotential and cycling performance decrease, indicating that an excessively thick conversion layer will increase interfacial transport resistance.
[0080] Comparative Example 4, which does not contain NH4HF2, shows insufficient activation of the natural oxide layer of the aluminum foil, a smaller conversion depth, and an inner-outer layer ratio that deviates from the preferred range.
[0081] Comparative Example 5, which only underwent fluorine-containing activation without the addition of a phosphonic acid precursor, failed to form an Al-OP-containing regulatory outer layer. Both exhibited lower performance than the complete HEDP / NH4HF2 system, indicating that limited activation and phosphonic acid coordination layering need to be used in combination.
[0082] (2) Different surface treatment processes have a certain impact on the performance of the prepared in-situ conversion nano-bottom current collector.
[0083] Examples 1-5 used the same HEDP / NH4HF2 system, only changing the concentration, time, and temperature. Table 2 shows that as the conversion depth increased, the nucleation overpotential first decreased and then slightly increased, indicating that the effect does not necessarily come from a deeper conversion depth. Examples 3 and 4 showed a good balance between nucleation overpotential, first-cycle coulombic efficiency, and cycle retention rate.
[0084] Examples 6-8 illustrate that the conversion solutions using different phosphonic acid precursors have varying effects, and N or B can be introduced into the control outer layer without introducing free particles to adjust the performance of the in-situ conversion nano-bottom layer current collector.
[0085] The exemplary embodiments of this application have been described above. However, the scope of protection of this application is not limited to the above embodiments. Any modifications, equivalent substitutions, improvements, etc., made by those skilled in the art within the spirit and principles of this application should be included within the scope of protection of this application.
Claims
1. An in-situ conversion type nano-layer current collector, characterized in that: The invention includes an aluminum foil substrate and a nano-bottom layer disposed on the surface of the aluminum foil substrate, wherein the nano-bottom layer is formed in situ from the surface of the aluminum foil substrate; the nano-bottom layer includes an anchoring inner layer and a regulating outer layer, wherein the anchoring inner layer is located on the side close to the aluminum foil substrate, and the regulating outer layer is located on the outside of the anchoring inner layer, i.e., on the side facing the electrolyte.
2. The in-situ conversion type nano-layer current collector according to claim 1, characterized in that: The in-situ conversion refers to treating the surface of an aluminum foil substrate with a conversion solution, wherein the conversion solution includes at least a phosphonic acid-type surface reaction precursor and ammonium hydrogen fluoride.
3. The in-situ conversion type nano-layer current collector according to claim 1, characterized in that: The anchoring inner layer contains one or more of Al-OP, Al-F and Al-OF bonding structures and is continuously connected to the surface layer of the aluminum foil substrate.
4. The in-situ conversion type nano-layer current collector according to claim 1, characterized in that: The outer layer of regulation is mainly composed of an aluminum phosphonate network, and retains P-OH, P=O, or boron- or nitrogen-containing polar sites.
5. A method for preparing the in-situ conversion type nano-substrate current collector as described in claim 1, characterized in that: Includes the following steps: (1) Provide aluminum foil with a thickness of 8-20μm, first degrease it, and then clean it with deionized water; (2) Prepare a conversion solution, wherein the conversion solution contains at least a phosphonic acid-type surface reaction precursor and ammonium bifluoride, and adjust the pH of the conversion solution to 2.5-4.5; (3) Contact at least one side of the aluminum foil with the conversion solution at 20-60℃ for 10-180s; then rinse with deionized water, pre-dry at 60-100℃ for 0.5-5min, and then heat-treat at 100-160℃ for 1-10min. (4) Cool and roll up to obtain an in-situ conversion type nano bottom current collector.
6. The method for preparing an in-situ conversion type nano-substrate current collector according to claim 5, characterized in that: In step (2): the conversion solution uses deionized water as a solvent, and based on the total mass of the conversion solution, the mass content of the phosphonic acid type surface reaction precursor is 0.2%-2.0%; the mass content of ammonium bifluoride is 0.01%-0.15%.
7. The method for preparing an in-situ conversion type nano-substrate current collector according to claim 5, characterized in that: The phosphonic acid-type surface reaction precursor is selected from any one or a combination of 1-hydroxyethylidene-1,1-diphosphonic acid, aminotrimethylenephosphonic acid, phytic acid, and vinylphosphonic acid; based on the total mass of the conversion solution, the mass content of the phosphonic acid-type surface reaction precursor is 0.4%-1.5%.
8. The method for preparing an in-situ conversion type nano-substrate current collector according to claim 5, characterized in that: In step (2): the conversion solution also contains boric acid or borate, and the mass fraction of boric acid or borate is 0.02%-0.3% based on the total mass of the conversion solution.
9. The application of the in-situ conversion nano-bottom current collector as described in claim 1 in a negative electrode-free sodium metal battery.
Citation Information
Patent Citations
Preparation method of multi-layer composite current collector
CN117810456A
Negative-electrode-free sodium ion battery current collector, preparation method and application thereof, and negative-electrode-free sodium ion battery
CN120149422A
Aluminum-based current collector for lithium battery and preparation method of aluminum-based current collector
CN120809831A